Using Organic Synthesis and Chemical Analysis to Understand the Photochemistry of Spore Photoproduct and Other Pyrimidine Dimers - Li, Lei (Synlett, 2018)
Pyrimidine dimerization is the dominant DNA photoreaction occurring in vitro and in vivo. Three types of dimers, cyclobutane pyrimidine dimers (CPDs), pyrimidine (6-4) pyrimidone photoproducts (6-4PPs), and the spore photoproduct (SP), are formed from the direct dimerization process; it is of significance to understand the photochemistry and photobiology of these dimers. Traditionally, pyrimidine dimerization was studied by using the natural pyrimidine residues thymine and cytosine, which share similar chemical structures and similar reactivity, making it sometimes less straightforward for one to identify the key pyrimidine residue that needs to be excited to trigger the photoreaction. We thus adopted synthetic chemistry to selectively modify the pyrimidine residues or to introduce pyrimidine analogs to the selected positions before UV irradiation is applied. By monitoring the subsequent outcomes from the photoreaction, we were able to gain unique mechanistic insights into the photochemistry of SP as well as of CPDs and 6-4PPs. Moreover, our approaches have resulted in several useful “tools” that can facilitate the understanding of lesion photobiology. Our results summarized in this account illustrate what organic synthesis/chemical analysis may allow us to achieve in future DNA lesion biology studies. 1 Introduction 2 Using the Deuterium Labeling Strategy to Understand SP Formation 3 Using Microcrystals to Reveal the Reaction Intermediates in SP Formation 4 Using a Phosphate Isostere to Understand the SP Structure 5 Synthesis of SP Phosphoramidite and SP Structural Studies 6 Using a Thymine Isostere to Understand CPD Formation 7 Using a Thymine Isostere to Understand 6-4PP Photoreaction 8 Understanding the Chemical Stability of SP 9 Understanding the Chemical Stability of 6-4PP10 Summary and Perspectives for Future Research
Keywords: chemical synthesis; pyrimidine dimers; spore photoproduct; cyclobutane pyrimidine dimers; pyrimidine (6-4) pyrimidone; photoproduct; photoreaction